A first exploration regarding gender segregated green entrepreneurship in Norrbotten and indications of theory that might be of interest. - Udén, Maria (Luleå tekniska universitet, Människa och teknik, 2024)
The GENGREEN project's main objective is to develop a cross-border recognized program for green entrepreneurial training directed to women. This is a first report on the Status of (Gender segregated) Green Entrepreneurship from the Swedish Partner Luleå University of Technology. About 3 500 women in Norrbotten may be counted as entrepreneurs. This would cover business owners in executive positions and self-employment. One topic of interest concerns the percentage of women entrepreneurs at regional level, who focus on sustainable/green activities. No data or estimation that can shed light on this could be identified. Regarding Norrbotten's “Green transitions”, the current trend is investments in heavy industry that generate entrepreneurial opportunities in male dominated branches. Relevant training and applicable formal education for green women entrepreneurs are offered by among other, ALMI and Luleå University of Technology. Interreg Gengreen